The Relationship Between Growth Mindset and Self-Efficacy of Nurses at Hospital 'X' in Bandung during The COVID-19 Pandemic - Trisa Genia C. Zega; Yuni Megarini C.; Meilani Rohinsa; Christopher Mario (Green Publisher Indonesia, 2025)
The COVID-19 pandemic has placed extraordinary demands on nurses, increasing their workload and emotional pressure, particularly at Hospital